2006
DOI: 10.1097/01.hp.0000196112.94905.dd
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Doses to Patients From Extracorporeal Shock Wave Lithotripsy

Abstract: The aim of this study was to determine the radiation doses to patients during extracorporeal shock wave lithotripsy (ESWL) and compare them with the available bibliographical data. In this method localization of the renal stones is attained by the use of fluoroscopy, and thus ESWL is included among those medical practices associated with patient radiation exposure. The entrance surface dose was measured using 3-4 thermoluminescent dosimeters positioned on the patients' backs at the entrance surfaces of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…However, it must be remembered that the dose from ESWL is always added to the dose from pre-and post-treatment KUB and intravenous urography procedures (Sandilos et al, 2006). For other urological procedures, typical effective doses range from <1 mSv for abdominal radiography to a mean of approximately 7 mSv for nephrostomy.…”
Section: Levels Of Radiation Dosementioning
confidence: 99%
“…However, it must be remembered that the dose from ESWL is always added to the dose from pre-and post-treatment KUB and intravenous urography procedures (Sandilos et al, 2006). For other urological procedures, typical effective doses range from <1 mSv for abdominal radiography to a mean of approximately 7 mSv for nephrostomy.…”
Section: Levels Of Radiation Dosementioning
confidence: 99%
“…Imaging studies may also be performed for other purposes. Also, the operator's exposure to ionizing radiation should be taken into account [18]. Interestingly, however, Ordon and colleagues demonstrated that a small but significant increase in fluoroscopy time correlated with an increase in SWL success rates [19].…”
Section: Discussionmentioning
confidence: 99%
“…1b), and the strategy adopted almost universally by ESWL operators is to deliver a predefined number of shockwaves (typically around 3,000). Finally, the operator has a significant role in minimizing the ionizing radiation exposure by restricting the fluoroscopy exposure time and number of spot films within the constraint of achieving accurate shockwave targeting of the stone (Sandilos et al 2006). More information on treatment progress and targeting during clinical ESWL may allow the operator to exercise greater control over many of the factors that influence retreatment rate and morbidity.…”
Section: Introductionmentioning
confidence: 99%